Global phylogenomic diversity of Brucella abortus: spread of a dominant lineage - Janke, Nicolette R.; Williamson, Charles H. D.; Drees, Kevin P.; Suárez-Esquivel, Marcela; Allen, Adrian R.; Ladner, Jason T.; Quance, Christine R.; Robbe-Austerman, Suelee; O’Callaghan, David; Whatmore, Adrian M.; Foster, Jeffrey T. (Frontiers in Microbiology, 2023)
Brucella abortus is a globally important zoonotic pathogen largely found in cattle hosts and is typically transmitted to humans through contaminated dairy products or contact with diseased animals. Despite the long, shared history of cattle and humans, little is known about how trade in cattle has spread this pathogen throughout the world. Whole genome sequencing provides unparalleled resolution to investigate the global evolutionary history of a bacterium such as B.abortus by providing phylogenetic resolution that has been unobtainable using other methods.We report on large-scale genome sequencing and analysis of B. abortus collected globally from cattle and 16 other hosts from 52 countries. We used single nucleotide polymorphisms (SNPs) to identify genetic variation in 1,074 B. abortus genomes and using maximum parsimony generated a phylogeny that identified four major clades. Two of these clades, clade A (median date 972 CE; 95% HPD, 781-1142 CE) and clade B (median date 150 BCE; 95% HPD, 515 BCE-164 CE), were exceptionally diverse for this species and are exclusively of African origin where provenance is known. The third clade, clade C (median date 949 CE; 95% HPD, 766-1102 CE), had most isolates coming from a broad swath of the Middle East, Europe, and Asia, also had relatively high diversity. Finally, the fourth major clade, clade D (median date 1467 CE; 95% HPD, 1367-1553 CE) comprises the large majority of genomes in a dominant but relatively monomorphic group that predominantly infects cattle in Europe and the Americas. These data are consistent with an African origin for B. abortus and a subsequent spread to the Middle East, Europe, and Asia, probably through the movement of infected cattle. We hypothesize that European arrival to the Americas starting in the 15th century introduced B. abortus from Western Europe through the introduction of a few common cattle breeds infected with strains from clade D. These data provide the foundation of a comprehensive global phylogeny of this 3 important zoonotic pathogen that should be an important resource in human and veterinary epidemiology.